Late Jurassic Sunosuchus (Crocodylomorpha, Neosuchia) from the Qigu Formation in the Junggar Basin (Xinjiang, China) - R. Schellhorn; D. Schwarz-Wings; M. W. Maisch; O. Wings (Fossil Record, 2009)
Various bone fragments of the crocodylomorph Sunosuchus from the Late Jurassic (Oxfordian) Qigu Formation in the southern Junggar Basin (Xinjiang Province/China) can be assigned to a single specimen and comprise the occipital region of the skull, mandibular fragments, and few postcranial elements. The size of the reconstructed skull does not exceed 30 cm in length and 13 cm in width. After comparison with other Sunosuchus species, the generic diagnosis of the genus can be expanded with the character of a lobe-like and unsculptured posterolateral process of the squamosal. The specimen is the first evidence of a crocodylomorph from the Qigu Formation and extends the geographical and stratigraphical range of Sunosuchus. doi:10.1002/mmng.200800010